Shaping the Corporate Perimeter in a Changing Media Industry. Issue 2 (2nd April 2020) - Oliver, John J.; Picard, Robert G.
ABSTRACT: A constant theme in strategic media management literature is the transformational impact that digital media technologies and deregulation have had on shaping media firms' corporate strategies. Whilst the role of corporate strategy is to encapsulate a firm's long-term direction and scope of activities, it will also give a strong indication of how the firm will compete and be positioned in an industry. However, the transformative effects of a highly technological media environment have changed our traditional view of how the media industry is defined, and so developing a strategic recipe for competing in an ill-defined industry becomes more challenging. This paper examines a single media firm's corporate strategy and perimeter and considers this in the context of a changing media industry. The paper takes a practice-led approach by undertaking a longitudinal analysis of a firm's acquisition and divestment activities in order to understand its corporate perimeter and by implication the industry or industries where it competes. We argue that by exploring a media firm's corporate strategy and perimeter over time, scholars will not only be able to better understand the dynamics of media practice and strategy, but also gain an insight into the changing nature of the media industry. The paper concludes that the 'five forces framework' on industry structure, profitability and attractiveness remains a relevant form of strategic analysis that can help media management researchers to conceptualize and understand the evolution of media firm corporate perimeter and the industries in which they compete.